The Commit to Be Fit framework: a community case study of a multi-level, holistic school-based wellness initiative in rural Virginia - Redelfs, Alisha H.; Smith, Madeleine; Merrill, Jacinda A.; Grimsley, Shannon; Jenkins, Hollyann E.; Tederick, Jacqueline S.; Butler, Amanda G.; Dueck, Kirsten; Eastham Thomas, Margy; Perez, David A.; Whigham, Leah D. (Frontiers in Public Health, 2023)
Background Public health interventions that target children's physical, mental, and emotional health will enhance their ability to learn and grow. Although more complex, school initiatives that address multiple ecological levels and take a holistic view may be more effective and likely to lead to lasting change. Aims This article presents the framework of Commit to Be Fit (C2BF) as an example of how schools can integrate multi-level and holistic approaches for health. This innovative school-based intervention includes activities addressing individual, home, school, and community to create a culture of wellness. We describe the implementation of C2BF and its basis in ecological models and give examples of activities across three components: cafeteria, classroom, and community. We discuss challenges and note that leadership engagement and alignment were critical elements for C2BF's success thus far. Discussion C2BF uses a school-based multi-level approach to creating a culture of wellness and holistic health for students, teachers, and community members. C2BF is unique compared to other school-based programming and includes activities that address all eight domains posited for program sustainability within public health. Built to be flexible and adaptive, C2BF was able to successfully pivot during the COVID pandemic and also follow new science. Conclusion C2BF and other multi-level holistic approaches are more likely to achieve long-term change by utilizing strategies across the multiple levels of the ecological model to improve health and wellbeing.